Agreement between Kinovea video analysis and the Open Barbell System for resistance training movement outcomes - Carzoli, J. P.; Sousa, C. A.; Helms, E. R.; Zourdos, M. C. (Journal of Human Kinetics, 2022)
The purpose of this study was to examine the agreement between Kinovea video analysis software and the previously validated Open Barbell System (OBS) for assessing average concentric and eccentric velocity, eccentric duration, peak concentric velocity, height of peak concentric velocity, and concentric and eccentric range of motion. Sixteen resistance-trained males performed 11 repetitions at various intensities (between 60-100% of one-repetition maximum) on both the back squat and the bench press. For each repetition, all outcome measures were assessed with Kinovea and the OBS. Agreement between devices for each outcome measure was analyzed with paired t-tests, intraclass correlation coefficients with 95% confidence intervals, Bland-Altman plots, and folded empirical cumulative distribution plots (Mountain plots). All outcome variables were found to be statistically different (i.e. they did not agree) between the two devices (p < 0.001), except for average eccentric velocity (p = 0.315), as determined by the paired t-tests. Mountain plots had long tails for every outcome measure and Bland-Altman plots showed large limits of agreement for all outcome measures except concentric range of motion and the height of peak concentric velocity, demonstrating low agreement between devices. Based upon these findings and the previous validation of the OBS, these devices should not be used interchangeably.